Developmental paths and activities of successful sport coaches - Gilbert, W.; Côté, J.; Mallett, C. (International Journal of Sports Science and Coaching, 2006)
The purpose of this research report is to present an overview of an on-going, international project designed to chart the developmental paths and activities of sport coaches. This brief report includes three sections: (a) conceptual framework used to guide the project, (b) project design and methodology, and (c) results from pilot studies with a sample of 15 successful coaches working in different sport contexts in the United States. Unlike the findings for athletic profiles, where several trends across coaching contexts were evident, only one trend was found in how these diverse groups of coaches invested their time in coach developmental activities. In relation to other coaching activities very little time was devoted to formal coach education on an annual basis. The results reinforce the need to consider the coaching context when examining coach development and when designing coach development initiatives.